2013
DOI: 10.4161/auto.22482
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy restrictsChlamydia trachomatisgrowth in human macrophages via IFNG-inducible guanylate binding proteins

Abstract: Interferon γ (IFNG) is a key host response regulator of intracellular pathogen replication, including that of Chlamydia spp The antichlamydial functions of IFNG manifest in a strictly host, cell-type and chlamydial strain dependent manner. It has been recently shown that the IFNG-inducible family of immunity-related GTPases (IRG) proteins plays a key role in the defense against nonhost adapted chlamydia strains in murine epithelial cells. In humans, IFN-inducible guanylate binding proteins (hGBPs) have been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
111
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 51 publications
2
111
1
Order By: Relevance
“…IFNγ priming induces GBP-mediated cell-autonomous immunity that results in the degradation of C. trachomatis inside autophagolysosomes (24,27). Because antimicrobial autophagy (also called xenophagy) often depends on host-mediated ubiquitination of invading microbes (28), we asked whether IFNγ priming would lead to the accumulation of ubiquitin on C. trachomatis PVs (referred to henceforth as "inclusions" in agreement with accepted nomenclature).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFNγ priming induces GBP-mediated cell-autonomous immunity that results in the degradation of C. trachomatis inside autophagolysosomes (24,27). Because antimicrobial autophagy (also called xenophagy) often depends on host-mediated ubiquitination of invading microbes (28), we asked whether IFNγ priming would lead to the accumulation of ubiquitin on C. trachomatis PVs (referred to henceforth as "inclusions" in agreement with accepted nomenclature).…”
Section: Resultsmentioning
confidence: 99%
“…Because GBPs mediate IFNγ-induced cell-autonomous resistance to C. trachomatis infections (24,27,40), we next asked whether the diminished targeting of GBPs to PVs in p62 −/− and TRAF6 −/− cells would debilitate the cell-autonomous defense system of the host cell. We found that IFNγ-primed cells lacking either p62 or enzymatically active TRAF6 elicited a less effective cell-autonomous immune response to C. trachomatis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the observation of tethering underlines the functional similarity of GBPs with atlastins and also other dynamin family members as recently shown for mitofusin (53). Recent studies on the antibacterial effect of GBPs indicate that hGBP1 and 2 are recruited to bacterial inclusions of Chlamydia trachomatis and trigger their rerouting for lysosomal degradation (54). It is tempting to speculate that the tethering effect of hGBP1 and its localization along the phagolysosomal pathway, which we report here, could be the basis for the physiological function of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike epithelial cells, M are not a hospitable niche for chlamydial intracellular replication, as illustrated by the fact that compared to the case in epithelial cells, only a small fraction of chlamydial RBs are detected in M (49). C. trachomatis destruction inside M has been associated with host cell autophagy, a process by which cells degrade cytoplasmic proteins and organelles (49)(50)(51). Also, studies have demonstrated that M autophagy can enhance antigen presentation to T cells (52).…”
mentioning
confidence: 99%